The ironic apocalypse in the novels of Leopoldo Marechal - Cheadle, Norman, 1953- (Woodbridge, Suffolk, UK ; Rochester, NY, USA : Tamesis, 2000)
Leopoldo Marechal has become a chosen precursor of many contemporary Argentine writers, cineastes, and intellectuals, and so his novels - universally recognized but rarely studied - demand treatment from a contemporary critical sensibility. This study departs from the line of criticism that reads Marechal as a Christian apologist, arguing instead that Marechal's 'metaphysical' novels are really metafictional, ludic exercises informed by ironic scepticism.
Adán Buenosayres: parodic revelation -- Metahistory and the cycle of language -- Light against darkness: poetry versus science -- Schultze and "el viaje a la oscura ciudad de Cacodelphia" -- Textual apocalypse: El banquete de Severo Arcángelo -- Coda and conclusion: Samuel Tesler's last word in Megafón, o la guerra.
Includes bibliographical references (pages 157-165) and index.
Print version record.
JSTOR
Keywords: Marechal, Leopoldo, -- 1900-1970 -- Criticism and interpretation; Marechal, Leopoldo, -- 1900-1970; Politics in literature; LITERARY CRITICISM -- American -- Hispanic American; Politics in literature; Criticism, interpretation, etc